Improving Learning Outcomes in Short Distance Running through the Discovery Learning Approach in Class VII Students of SMP Negeri 4 Bendahara - Suprayetno (Marga: Journal Of Innovation and Creatifity, 2023)
The general objective of this research is to enhance student outcomes through the implementation of Short-Distance Running Learning using discovery learning. Additionally, this study aims to obtain in-depth information about the application of short-distance running using discovery learning. The research design employed is Classroom Action Research (CAR). The subjects in this study are 29 students from class VII at SMP Negeri 4 Bendahara. The research was conducted over two meetings spanning two cycles. Each cycle consisted of three sessions. The first cycle indicated that through action, students can self-motivate. From this first cycle, the result was 0%, indicating it was incomplete. The second cycle, as a reflection of the first cycle, also demonstrated that action improves student learning outcomes. The result of the second cycle was 96%, indicating completion. Based on the findings of this research, it can be concluded that: (1) Short-distance running learning using discovery learning enhances student learning outcomes, (2) Short-distance running learning using discovery learning motivates students and encourages active participation in the learning process.